Analysis of Company Profitability at PT Arita Prima Indonesia Tbk - Saputri, Anggita Dwi; Taba, Muh. Idrus; Hakim, Wardhani (Economics and Business Journal (ECBIS), 2023)
The Analysis of Company Profitability at PT Arita Prima Indonesia Tbk. This study aims to determine and analyze the level of profitability of PT Arita Prima Indonesia Tbk. The analytical method used in this research is quantitative descriptive analysis using the Du Pont System. The research results indicate that the decline in profitability at PT Arita Prima Indonesia Tbk in 2017, as identified by the Du Pont System, was caused by the company's ineffective utilization of its long-term investments, resulting in a decrease in net income by 12.29%